2022
DOI: 10.3389/fnut.2022.1048632
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of pulsed electric field in the fermented wine industry

Abstract: Fermented wine refers to alcoholic beverages with complex flavor substances directly produced by raw materials (fruit or rice) through microbial fermentation (yeast and bacteria). Its production steps usually include saccharification, fermentation, filtration, sterilization, aging, etc., which is a complicated and time-consuming process. Pulsed electric field (PEF) is a promising non-thermal food processing technology. Researchers have made tremendous progress in the potential application of PEF in the ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 96 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…For the IC 50 value of radical assay, the ratio of high-M w and medium-M w component showed a positive correlation ( p < 0.05), while the ratio of the low-M w component demonstrated a negative correlation ( p < 0.05), indicating that the Noni polysaccharide with a smaller molecular weight showed better radical scavenging ability. Previous studies also reported the superior antioxidative ability of low-molecular-weight polysaccharides, which was attributed to their larger surface area and greater water solubility facilitating the reaction with radicals ( 34 , 35 ). From Table 4 , the contents of uronic acid and GalA also displayed a significant linear correlation with the IC 50 value of hydroxyl assay with the coefficient of –0.991 and –0.913 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…For the IC 50 value of radical assay, the ratio of high-M w and medium-M w component showed a positive correlation ( p < 0.05), while the ratio of the low-M w component demonstrated a negative correlation ( p < 0.05), indicating that the Noni polysaccharide with a smaller molecular weight showed better radical scavenging ability. Previous studies also reported the superior antioxidative ability of low-molecular-weight polysaccharides, which was attributed to their larger surface area and greater water solubility facilitating the reaction with radicals ( 34 , 35 ). From Table 4 , the contents of uronic acid and GalA also displayed a significant linear correlation with the IC 50 value of hydroxyl assay with the coefficient of –0.991 and –0.913 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…In the food industry, color is one of the important parameters of food ingredients and affects the acceptability of food products by consumers ( 25 ). In addition, changes in food color help us to distinguish changes in the physical and chemical properties of raw food materials ( 26 ). The WI of bagasse increased from 67.69 to 84.05, which can significantly increase consumer acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial tension (IFT) was measured by pendant drop procedure with a tensiometer (DSA25, Kruss Ltd., Germany) (Lin et al ., 2020b). A pendant drop (25 μL) of sample solution (10 mg/mL in water) was injected by a needle immersed into MCT and captured by a CCD camera to determine the IFT at 25 °C (Feng et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%